Tabu Bahasa dalam Kekerabatan Keluarga Masyarakat Angkola - Nasution, Jamaluddin; Tengku, Thyrhaya Zein; Maharani, Puan; Sanjaya, Dedi; Kudratov, Laziz Farkhodovich (Linguistik, Terjemahan, Sastra (LINGTERSA), 2026)
The study aims to find personal patterns of forbidden communication in Angkola Language (BA), to figure out the performance and communication patterns as well as the values ​​and reasons for the prohibition. Another goal is to re-awaken the youth to apply the values ​​and norms in BA in the freedom era of communication. The research carries out qualitative approach with the ethnographic method of anthropolinguistics framework, it studies language in a cultural framework. Participants involved in BA which are considered taboo in communication are between: 1) the wife/husband of the brother-in-law called ompung bayo; 2) siblings, especially in different sex; 3) daughter-in-law to son-in-law; 4) son-in-law to daughter-in-law; and 5) in-law parent relationship (a husband’s father and a wife’s mother). The performance patterns carried out by the participants were: 1) silent and not answer; 2) indirect sentences; 3) coding (coughing sound); 4) simple and short words; 5) mediation of surrounding objects; 6) leaving the conversational location; 6) not joking; 7) tending to be serious; 8) giving polite answers; 9) avoiding jokes, and long talk; 10) using a third person intermediary; and 11) making small talk. The indexicality of this language is: 1) respect; 2) the attitude of maintaining self-respect and respect for brothers; 3) polite attitude; 4) form of service; and 5) reluctance to speak. The results of the respondents' answers indicate that the level of understanding is 63.13% and the ignorance is mostly from respondents aged under 20 years. The cause of the waning of language taboo culture is due to the development of the times (globalization), the widespread use of social media and the openness in information and communication in today’s modern era.